Sustainability of Construction Aggregates in Kuwait - Al-Fadala, Sharifa (ARCHive-SR, 2019)
Kuwait is facing a current construction boom with projects worth of more than USD188bn. The huge infrastructure spending plan of Kuwait is reflected with a growing demand of concrete as concrete is the most commonly used building material in the local construction. At the present, the quarrying of coarse aggregate which is a main concrete constituent material is banned in Kuwait since 1997 and construction industry depends on the imported coarse aggregates from neighbouring sources such as United Arab Emirates and Iran. Kuwait is also interested in challenging the growing concern of an effective environmental management of water, land and atmosphere to achieve a sustainable civilization. The increasingly environmental pressures coupled with the limited available economical resources are causing the decision making authorities to consider the practice of recycling and waste utilization. This paper presents Kuwait Institute for Scientific Research (KISR) efforts to investigate sustainable sources of coarse aggregate for construction industry from waste. The first sustainable source investigated is the production of synthetic lightweight aggregates utilizing combinations of argillaceous indigenous and waste materials, and the second is recycled aggregates from construction and demolition wastes. The potential of the two sustainable sources of construction aggregates are presented and the needed steps for real industrial application are addressed.